The labor migration industry for health and educational services: Regulatory and governance structures and implications for national development - Tullao, Tereso S., Jr. (Animo Repository, 2010)
The analysis on the implications of the temporary migration of Filipino workers on national development and policy reforms should be viewed in terms of the push and pull factors, the labor and demographic asymmetries, and the forces of globalization that affect external migration. In addition, the pressure of labor and demographic asymmetry between sending and receiving countries together with the forces of globalization make the profitability of investment in temporary migration more realistic and less probabilistic. The labor shortages in the recipient countries caused by domestic and global economic factors make the expected income very high in the computation of the rate of return to temporary migration. Given the high rates of return, and the attractiveness of overseas employment, and the highly globalized labor market, the optimal strategy for the government is to manage temporary labor migration so that the benefits are enhanced and social costs mitigated. In terms of enhancing positive contributions of migration, remittances can be channeled to productive uses particularly in tempering its impact on the overvaluation of the real exchange rate. It can also be utilized in augmenting the supply of sectors producing human capital. Through these supply enhancing activities the price effect of the appreciation of the real exchange rate due to remittance inflows may be eased and at the same time improve the productivity of the workers seeking overseas employment. Although expected private returns to education and migration are high, decisions to go to school and migrate are usually accompanied by huge social costs. Because individuals do not consider these social costs they continue to invest because the expected private return private is still quite high. As a result, thousands of students are prepared to take the various risks until they are able to migrate and reap the returns on their investments. This, on the other hand, has created distortions in terms of a misallocation of resources and has created a pool of unemployed and undemployed. To mitigate the social costs of migration, there is a need to improve the deployment procedures, increase the probability of external employment and enhance the protection mechanisms of workers abroad. In terms of policy retorms, the inadequacy of mitigating outflow of Filipino workers through liberalization measures in the factor markets may lead us to look at the supply dimension instead of demand aspects in the labor market. One way of lessening the outflow is to make the wage rate differential as small as possible by rapid economic growth and the promotion and implementation of a more enlightened population program that can moderate the increases in the supply of labor and in the long run put pressure for increased wage rate. In this case temporary migraton will now be a choice and no longer a necessity for Filipino workers.